Projeto de um oxímetro com sensor de orelha utilizando o método reflexivo - Gnatkovski, Victor Hugo Celoni (2021)
The pulse oximeter is a medical device used to monitor blood oxygen saturation (S pO2) using the photoplethysmography technique. Most oximeters are designed to be used in peripheral regions such as a finger or earlobe. However, these locations are subject to external problems that can result in noise and inaccuracies. In an attempt to overcome these problems, a reflective method oximeter prototype was designed for use in the ear shell as an alternative site for measuring oxygen saturation. The prototype was developed using the MAX30100 sensor and the ESP8266 microcontroller and the tests were carried out in comparison with a commercial oximeter. The results indicated that the ear concha may be a viable alternative for obtaining oxygen saturation.